Study of tomato growers' cultural practices and risks associated with the unreasoned use of chemical inputs in the Adamawa Region, Cameroon - Ramsès Tsala; Zacharie Bounyahré Mounkéné; Gaston Dimitri Amia; Maïmouna Abba; Lucien Tatchum Tchuenteu; Clautilde Megueni (African and Mediterranean Agricultural Journal - Al Awamia)
To improve tomato productivity, farmers generally use chemical fertilizers and pesticides. Although these inputs have proven beneficial effects, their non-reasoned use, through non-compliance with approved doses, poor management of agricultural chemical packaging, and failure to respect re-entry times after application, can have harmful effects on the environment and the health of living beings. In this respect, a study aimed at characterizing cultivation practices among tomato growers in the Bini-Dang area (Adamawa-Cameroon) was carried out in order to assess the risks associated with the use of chemical fertilizers and pesticides. The snowball sampling method, together with visual diagnostics, enabled information to be collected from 180 tomato growers in the said locality. On average, 93% of growers use chemical inputs; 83% of these growers do not respect the approved doses of these products, and around 82% of growers do not provide themselves with Personal Protective Equipment. Finally, a non-negligible proportion (over 50% in total) do not respect re-entry times after application of agricultural chemicals. These poor practices can lead to cancerous diseases, spontaneous abortions, lower IQs and the degradation of ecosystem biodiversity. The practices used by Bini-Dang tomato growers therefore present health and environmental risks, and the search for alternative methods for sustainable agriculture remains a necessity.